Application of swine manure on agricultural fields contributes to extended-spectrum β-lactamase-producing Escherichia coli spread in Tai'an, China - Gao, Lili; Hu, Jiaqing; Zhang, Xiaodan; Wei, Liangmeng; Li, Song; Miao, Zengmin; Chai, Tongjie (Frontiers in Microbiology, 2015)
The prevalence of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (E. coli) is increasing rapidly in both hospital environments and animal farms. A lot of animal manure has been directly applied into arable fields in the developing countries. But the impact of ESBL-positive bacteria from animal manure on the agricultural fields is sparse, especially in the rural regions of Tai’an, China. Here, we collected 29, 3, and 10 ESBL-producing E. coli from pig manure, compost, and soil samples, respectively. To track ESBL-harboring E. coli from agricultural soil, these isolates of different sources were analyzed with regard to antibiotic resistance profiles, ESBL genes, plasmid replicons, and enterobacterial repetitive intergenic consensus (ERIC)-polymerase chain reaction (PCR) typing. The results showed that all the isolates exhibited multi-drug resistance. CTX-M gene was the predominant ESBL gene in the isolates from pig farm samples (30/32, 93.8%) and soil samples (7/10, 70.0%), but no SHV gene was detected. 25 isolates contained the IncF-type replicon of plasmid, including 18 strains (18/32, 56.3%) from the pig farm and 7 (7/10, 70.0%) from the soil samples. ERIC-PCR demonstrated that 3 isolates from the soil had above 90% genetic similarity with strains from pig farm samples. In conclusion, application of animal manure carrying drug-resistant bacteria on agricultural fields is a likely contributor to antibiotic resistance gene spread.